Molecular characterization, spatiotemporal expression, and background adaptation regulation of tyrosinase in loach ( Misgurnus anguillicaudatus ) - Zhixiong Li; Xinchen Wang; Le Guan; Muxin Liu; Hong Wang; Di Wu; Xiaobing Yi; Shaoqing Jian; Junqing Sheng (Journal of Fish Biology, 2024)
The Poyang Lake region is home to large‐blackspot loaches (LBL), small‐blackspot loaches (SBL), and non‐blackspot loaches (NBL), Misgurnus anguillicaudatus . To investigate the impact of tyrosinase on spot development, the complementary DNAs (cDNA) of tyrosinase in M. anguillicaudatus (designated as Matyr ) were cloned using the rapid amplification of cDNA ends (RACE)‐PCR method. The full‐length cDNA for Matyr was 2020 bp, and the open‐reading frame comprised 1617 bp, encoding a predicted protein with 538 amino acids. Phylogenetic studies revealed that MaTyr was first grouped with Tyr of Triplophysa tibetana and Leptobotia taeniops , and then Tyr of other cyprinid fish. The quantitative reverse‐transcription‐PCR results show that Matyr was highly expressed in the muscle, caudal fin, and dorsal skin. The Matyr gene's messenger RNA expression pattern steadily increased from the fertilized ovum period to the somitogenesis period, and from the muscle effect stage to 6 days after fertilization, it considerably increased ( p Matyr hybridization signals with similar location could be found in all developmental stages of three kinds of loaches using whole‐mount in situ hybridization (WISH) technology and were the strongest during the organ development period and melanin formation period. Dot hybridization signals in LBLs rapidly spread to the back of the body beginning at the period when the eyes first formed melanin, and their dimensions were larger than those of NBLs during the same time period. The body color of loaches could change reversibly with black/white background adaptation. The α‐msh , mitfa , and tyr are mainly expressed in loaches adapted with a black background. Tyr gene could be involved in the development of blackspots and body color polymorphism, and contribute to organ development in the loach.